The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/jcm9010256
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Femoral Varus Derotational Osteotomy for the Spastic Hip Displacement: Implication for the Indication of Concomitant Pelvic Osteotomy

Abstract: No previous studies have suggested a reliable criterion for determining the addition of a concomitant pelvic osteotomy by using a large patient cohort with quadriplegic cerebral palsy and a homogenous treatment entity of femoral varus derotational osteotomies (VDRO). In this retrospective study, we examined our results of hip reconstructions conducted without a concomitant pericapsular acetabuloplasty in patients with varying degrees of hip displacement. We wished to investigate potential predictors for re-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Park et al suggested that postoperative MPs > 5.1% were inflection points for hip redislocation after VDRO without pelvic osteotomy in nonambulatory children with CP. Their finding indicated that severely subluxated or dislocated hips and hips in which the femoral head is successfully reduced by VDRO, but is still contained within the dysplastic acetabulum, may benefit from the additional pelvic osteotomy [21] . Our results suggested that if Change MP immediately after VDRO was ≥79%, VDRO alone might maintain the repositioning of the hip until the final follow-up.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Park et al suggested that postoperative MPs > 5.1% were inflection points for hip redislocation after VDRO without pelvic osteotomy in nonambulatory children with CP. Their finding indicated that severely subluxated or dislocated hips and hips in which the femoral head is successfully reduced by VDRO, but is still contained within the dysplastic acetabulum, may benefit from the additional pelvic osteotomy [21] . Our results suggested that if Change MP immediately after VDRO was ≥79%, VDRO alone might maintain the repositioning of the hip until the final follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…Their finding indicated that severely subluxated or dislocated hips and hips in which the femoral head is successfully reduced by VDRO, but is still contained within the dysplastic acetabulum, may benefit from the additional pelvic osteotomy. [ 21 ] Our results suggested that if Change MP immediately after VDRO was ≥79%, VDRO alone might maintain the repositioning of the hip until the final follow-up. Because Change MP could be confirmed intraoperatively, a Change MP of ≤79% after VDRO might be an intraoperative predictor that should add a pelvic osteotomy.…”
Section: Discussionmentioning
confidence: 83%
“…Park et al in their study of 144 patients who underwent VDROs, with or without open hip reduction, studied the outcomes based on various radiological parameters [ 16 ]. They noticed satisfactory outcomes in 78.5% of hips.…”
Section: Discussionmentioning
confidence: 99%
“…All operative procedures were performed by the senior author, and the surgical techniques used were similar to those previously described 12 – 16 . Tenotomies of the adductor longus and gracilis and neurectomy of the anterior branch of obturator nerve were completed through a small transversal incision made in the groin.…”
Section: Methodsmentioning
confidence: 99%